Pengendalian Infestasi Ektoparasit (Agulus sp.) Pada Benih Ikan Mas (Cyprinus carpio) Dengan Menambahkan Garam (NaCl) di Pasar Ikan Hias Gunungsari Surabaya - Rahmawati, Indra; Putri, Agnes Salsabila; Roeswandono, Roeswandono; Sasmita, Rochiman (VITEK : Bidang Kedokteran Hewan, 2021)
This study aims to determine the effectiveness of adding salt (NaCl) to ectoparasite Argulus sp. which infested goldfish (seedsCyprinus carpio) from the Gunung Sari Ornamental Fish Market, Surabaya. This research was carried out by taking samples from one of the ornamental fish cultivation sites in Surabaya with a total of 250 goldfish seeds. This study used 25 containers as research media with 10 goldfish seeds each. Each treatment was repeated five times, namely with the salt concentration P1 = 54 grams/liter, P2 = 108 grams/liter, P3 = 162 grams/liter, P4 = the negative group or the untreated group and P5 = positive control using methylene. blue 3 grams/liter. Ectoparasite examination Argulus sp.. conducted at the Parasitology Laboratory, Faculty of Veterinary Medicine, Wijaya Kusuma University, Surabaya. The completely randomized design method (CRD) was used in the study. The results were tested by ANOVA and a significant value of 5% (α 0.05). The test results showed that the treatment with methylene blue was not significantly different from the treatment of the three salt concentrations which had the same effectiveness. So the ANOVA test results show that all treatments are not significantly different.